Socialization of Harmonization of Tax Regulations to Increase Tax-Compliant MSMEs in Pematang Serai Village - Destari Nurlaila Damanik; Yunita Sari Rioni (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The government has formulated the latest policy in taxation which is contained in Law Number 7 of 2021 concerning Harmonization of Tax Regulations or what we often hear about as the HPP Law. Based on the situation analysis, there are still many MSMEs who have not heard, understood, and understood the changes to these regulations. Therefore, this service activity involves MSMEs actors in Pematang Serai Village as participants in this Community Service activity. The stages in this activity start from analyzing the participant's situation, reviewing and formulating activities, socializing activities, and implementing community service. Based on the results of the service that has been carried out, it can be concluded that changes related to tax regulations make this socialization and training activity important. This aims to increase the knowledge of MSMEs actors as taxpayers regarding changes to existing tax regulations.